Climate engineering by enhancement of ocean alkalinity : Impacts on the Earth system and a comparison with solar radiation management - Ferrer González, Miriam (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
Climate engineering (CE) methods are intended to mitigate the environmental perturbations caused by anthropogenic climate change. Artificial ocean alkalinization (AOA) strengthens the ocean carbon sink whilst decreasing seawater acidity via enhancement of the buffering capacity. Solar radiation management (SRM) by stratospheric sulfur injection tempers surface warming through increasing the Earth’s albedo. For the first time, the CE-driven effects on the Earth system of large-scale AOA and SRM scenarios are consistently compared in a comprehensive Earth system model with interactive carbon cycle. Using the Max Planck Institute Earth System Model (MPI-ESM) forced by fossil-fuel CO2 emissions, I explore the impacts of these CE methods on the global carbon uptake and ocean biogeochemistry. I design and run AOA scenarios that reduce atmospheric CO2 levels to the trajectory of the Representative Concentration Pathway (RCP) 4.5 in a high CO2 world following the RCP8.5 scenario. The effects of these large-scale AOA scenarios on the Earth system are analyzed and compared to SRM simulations that target the radiative forcing of the RCP4.5 scenario under RCP8.5 forcing. Global addition of 114 Pmol of alkalinity into the surface ocean during the 21st century stabilizes atmospheric CO2 concentration to RCP4.5 levels under RCP8.5 emissions. The entire surface ocean turns into a carbon sink. Half of the CO2 emitted into the atmosphere (940 GtC) is removed by the ocean, preventing 1.5 K of global warming by 2100. Still, surface temperatures remain 0.5 K higher than the targeted RCP4.5, due to the unmitigated forcing of non-CO2 agents. The impacts of ocean acidification are largely offset, despite the enhanced carbon sink. However, as a side effect surface seawater pH and Ω exceed regionally historical levels, with potential adverse ecological effects. By 2100, much higher values of pH (up to 0.6 higher units) and Ω (fivefold increase) are reached over the Arctic Ocean while Ω doubles in tropical oceans. After termination of AOA ...